Surgical treatment of breast cancer liver metastases - A nationwide registry-based case control study. Issue 6 (June 2020) - Sundén, Marcus; Hermansson, Cecilia; Taflin, Helena; Andersson, Anne; Sund, Malin; Hemmingsson, Oskar
Abstract: Introduction: The benefit of liver resection or ablation for breast cancer liver metastases (BCLM) remains unclear. The aim of the study was to determine survival after isolated BCLM in nationwide cohorts and compare surgical versus systemic treatment regimens. Materials and methods: The Swedish register for cancer in the liver and the bile ducts (SweLiv) and the National register for breast cancer (NBCR) was studied to identify patients with 1–5 BCLM without extrahepatic spread diagnosed 2009–2016. Data from the registers were validated and completed by review of medical records. A Kaplan-Meier plot and log rank test were used to analyse survival. Prognostic and predictive factors were evaluated by Cox regression analysis. Results: A surgical cohort (n = 29) was identified and compared to a control cohort (n = 33) receiving systemic treatment only. There was no 90-day mortality after surgery. Median survival from BCLM diagnosis was 77 months (95% CI 41–113) in the surgical cohort and 28 months (95% CI 13–43) in the control cohort, (p = 0.004). There was a longer disease-free interval and more oestrogen receptor positive tumours in the surgical cohort. Surgery was a significant positive predictive factor in univariate analysis while a multivariable analysis resulted in HR 0.478 (CI 0.193–1.181, p = 0.110) for surgical treatment. Conclusion: Surgery for BCLM is safe and might provide a survival benefit in selected patients but prospective trials are warranted to avoid selection bias.